Optical coherence tomography detection of changes in inner retinal and choroidal thicknesses in patients with early retinitis pigmentosa - Akay,Fahrettin (2020)
ABSTRACT Purpose: To evaluate the inner retinal and choroidal thicknesses in patients with early retinitis pigmentosa. Methods: We analyzed spectral-domain optical coherence tomography images of 35 retinitis pigmentosa patients and 40 healthy individuals. We measured macular and ganglion cell complex thicknesses. We took choroidal thickness measurements in the subfoveal region and 500, 1,000, and 1,500 mm from the foveal center. Results: Patients with retinitis pigmentosa had significantly thinner macular thicknesses and choroidal thicknesses in all measurements, and their individual ganglion cell complex thickness measurements were lower than those in healthy individuals. The mean ganglion cell complex thickness was significantly lower in patients with retinitis pigmentosa than that in controls. The mean macular thickness was significantly correlated with the mean choroidal and mean ganglion cell complex thicknesses. (We found no correlation between the mean choroidal thickness and the mean ganglion cell complex thickness). Conclusions: The choroid was mildly affected in our patients with early retinitis pigmentosa. The tendency toward significance in the inner retina was possibly caused by a good visual acuity.